PENGARUH PERUBAHAN HARGA EMAS DUNIA DAN KURS RUPIAH PADA RETURN PASAR - Umi Murtini; Sirilus Kristiyo Amijoyo (Fakultas Bisnis UKDW, 2012)
This study aimed to examine the effect of gold price change and IDR exchange rate on marketreturn. Data used was weekly closing price over 2008 – 2012 period. Besed on multipleregression analysis, the results showed that gold price change had positive effect on marketreturn, while IDR exchange rate had negative effect.Keywords: gold price change, IDR exchange rate, market return.